Phytochemical Compounds and Antibacterial Test of Theonella cylindrica against Staphylococcus aureus and Escherichia coli - Mambo, Christi D.; Warouw, Finny; Nangoy, Edward; Rumengan, Inneke; Kepel, Billy; Bara, Robert (JURNAL BIOS LOGOS, 2025)
Infectious diseases are a health problem faced by developing countries like Indonesia. This disease is caused by bacteria that attack humans. Improper use of antibiotics can cause bacterial resistance to antimicrobials. Antimicrobial resistance is the most significant public health threat, resulting in greater demand for finding new effective antimicrobials from natural products such as sea sponges. This research aimed to test the antibacterial activity of Theonella extract against Staphylococcus aureus and Escherichia coli and determine the class of chemical compounds contained therein. Research stages include sampling, sample preparation and extraction, qualitative phytochemical screening, making solutions, media creation, and antibacterial testing. The research showed that sponges metabolite compounds consisted of alkaloids, flavonoids, tannins, saponins, and phenolics. The diameter of the inhibition zone at concentrations of 80% and 100% showed potential antibacterial activity but more strongly inhibited the growth of Staphylococcus aureus bacteria than Escherichia coli bacteria.